Frontal site surgery for chronic migraine therapy - Raposio, Giorgio; Antonini, Andrea; Gualdi, Alessandro; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2023)
Background: According to the most current theories, chronic inflammation of some cranial nerves give rise to an inflammatory chain that would result in migraines. As for frontally located attacks, the nerves involved are two (on each side): the supraorbital and the supratrochlear. Surgical treatment includes complete neurolysis of both of these nerves. Methods: In this work, we describe our experience with this type of surgery. From 2011 to 2022, we treated 98 cases suffering from chronic migraine not responsive to drugs with frontal localization. The results were evaluated through a specific questionnaire three months and one year after surgery. Results: After three months post-surgery, we observed a success rate (reduction of monthly attacks equivalent to or greater than 50%) in 87% of patients (32% complete recovery). These results were essentially confirmed one year after surgery. The rare complications (mainly paresthesias and dysesthesias of the frontal area) have always resolved spontaneously within a few months. Conclusion: The surgical approach allowed to obtain good therapeutic results with a low rate of complications.